To Conduct a Prospective Study on Pioglitazone Induced Kidney Injury in Tertiary Care Hospital - Archana, B.; Vishwada, Palla; Charani, Yallapragada Sahithi Sri; Shri, Dadi Sneha (Journal of Drug Delivery and Therapeutics, 2024)
Conducting a prospective study on kidney impairment caused by pioglitazone at tertiary care hospitals is the study's goal. The goal is to assess Pioglitazone, mortality, quality of life, and the degree of the medication's harmful side effects in diabetic patients. According to the "Pioglitazone-induced kidney injury" prospective study. Out of 350 trial participants, prolonged pioglitazone use in diabetic patients has been shown to raise serum creatinine levels by up to 11%. Additionally, individuals who have been using pioglitazone for six to ten years are more likely to experience renal injury, with males in the 50–60 year age range being the most common victims.Keywords: Pioglitazone, diabetic, prospective, tertiary care, hospital.